Study on Volatile Chemicals as Spoilage Indexes of Salmon by HS-SPME-GC-MS Technique during Non-Frozen Storage - Guanhua Xuan; Miaorong Guo; Hong Lin; Jianxin Sui; Jingxue Wang (Molecules, 2022)
Freshness is the most fundamental and important factor to assess raw fish quality. The purpose of our study was to determine the potential spoilage indexes of salmon during non-frozen storage by using headspace solid-phase microextraction (HS-SPME) followed by gas chromatography-mass spectrometry (GC-MS). More than 300 volatile compounds in salmon were detected when sensory scores declined gradually following the quality changes of salmon at different temperatures. And there were 27 and 31 compounds that showed concentration variations when stored at 4 °C and 25 °C, respectively. Among them, the contents of 1,3-di-tert-butylbenzene, acetic acid, and 3-methyl-1-butanol increased significantly in the later storage period and were in accordance with the salmon’s qualities. The present study provides valuable information on the volatile chemical spoilage indexes that are closely related to the freshness of salmon, which may provide an efficient alternative way for quality evaluation of salmon.